Nitrogen loads influence trophic organization of estuarine fish assemblages. (29th February 2016) - Warry, Fiona Y.; Reich, Paul; Cook, Perran L. M.; Mac Nally, Ralph; Thomson, James R.; Woodland, Ryan J.
Summary: Nutrient (N and P) loading may affect functioning in aquatic ecosystems by restructuring producer assemblages with flow‐on effects to consumers. Trophic niche occupancy and trophic organization of consumers are key components of ecosystem function that have been increasingly investigated using quantitative isotopic niche indices. These indices are based on the premise that the isotopic values of consumer tissues indicate their assimilated diet. Typically, isotopic niche indices are calculated using only consumer isotope data, which limit their application for spatial and temporal comparisons because consumer isotopic niches depend on isotopic variability of available autotrophs. We used measures of isotopic variability of autotrophs to standardize isotopic niche indices, which enabled us to compare trophic organization of fish assemblages in nine estuaries spanning a broad range of nutrient loading. We related standardized isotopic niche indices of fish assemblages to nitrogen and phosphorous loads and hydrological flushing of the estuaries in autumn and spring. The estuarine fish assemblages studied here showed greater trophic diversity and less redundancy given moderate to high inorganic nitrogen loading. Taxonomic richness partly influenced three isotopic niche indices measuring trophic diversity, but not measures of redundancy. Similar patterns may occur in other systems in which nitrogen loads have increased but the diversity of primary producers has not been reduced to a single dominant source. Our results demonstrate bottom‐up controls of estuarine food webs. Effects of inorganic nitrogen loading were transmitted upwards through the food web to affect the trophic organization of higher trophic levels, demonstrating the crucial role of nitrogen for estuarine trophic dynamics. Abstract : Lay Summary